CUSTOMERS SATISFACTION IN TELECOM SECTOR IN SAUDI ARABIA: AN EMPIRICAL INVESTIGATION - Sharma, Raj Bahadur (European Scientific Journal, ESJ, 2014)
Saudi Telecom Company (STC) and Mobily are the two most popular telecom companies in the Kingdom of Saudi Arabia. The purpose of present research is to investigate those factors which influence customer satisfaction in telecom industry in Riyadh region of Saudi Arabia. The study is based on primary data collected on the random basis from 150 customers of various telecom companies. The respondents were selected on random basis and were requested to express their feelings through a structured questionnaire. Simple mean, percentage, Chi-Square test were employed to analyze the data. The result indicated that customers are more satisfied with quality of service, network coverage, quality of SMS, mobile internet, customer service, promotion schemes of Saudi Telecom services (STC) as compare to others telecom companies in Saudi Arabia.